Pengaruh Indolebutyric Acid (IBA) Dan Naphthalene Acetic Acid (NAA) Terhadap Node Cutting Lada Varietas Lampung Daun Lebar - Zasari, Maera (Universitas Bangka Belitung, 2015)
Pepper seed availability in large amount and have high qualities are needed to support pepper development and production. Pepper multiplication by node cutting method is one of alternatives way to provide pepper seed in large amount and quickly. Root stimulation accelerates node-cutting growth and development providing well and uniform pepper seed vigorous with giving growth hormones, such as auxin. The research aimed to identify effect of Indolebutyric acid (IBA) and Naphthalene acetic acid (NAA); combine with Indolebutyric acid (IBA) and Naphthalene acetic acid (NAA) to pepper node-cutting development.The experiment used Complete Randomized Block Design with 25 traits hormone. Data analysis used Complete Randomized Block Design analysis of variance and significant test by Duncan in 95% probability. The results showed that growth hormones (IBA, NAA, and IBA + NAA) give similar effect to node-cutting growth in one node-tip. Pepper node-cutting development in one node-tip obtained by 2000-3000 ppm hormone concentration.